Open-ended narrative and moral formation - J. Klaasen (Acta Theologica)
A narrative approach for moral formation must take the shortcomings of abstract reason seriously. Two specific attempts to a narrative approach, narrative as a means to an end and the supra-narrative approach, do not address these shortcomings and are inadequate approaches for moral formation. An open ended narrative approach considers reason as an important phenomenon for moral formation. The shortcomings of using abstract reason such as the neglect of tradition, community and the particular finds relevance in the way reason is used in an open ended narrative approach. Reason is not rejected, but it is used in a more holistic way that includes critical reflection.